Na2O-Gd2O3-Al2O3-P2O5 glass scintillator doped with Dy3+: X-rays and proton responses - Wantana, N.; Kaewnuam, E.; Tariwong, Y.; Quang, Nguyen Duy; Pakawanit, P.; Phoovasawat, C.; Vittayakorn, N.; Kothan, S.; Kim, H. J.; Kaewkhao, J. (My University, 2023)
Dy3+:Na2O-Al2O3-Gd2O3-P2O5 (Dy:NAGP) glasses were fabricated to investigate the capability for radiation responses. The influence of Dy2O3 concentration on glass properties was studied. The density and effective atomic number of glass increased with the addition of Dy2O3 content. The glasses absorbed the photons in the ultraviolet, visible light, and near-infrared region. In photoluminescence (PL) spectra, the obvious yellow emission at 574 nm and blue emission at 482 nm of Dy3+ were both generated by the direct excitation and the Gd-Dy energy transfer. The PL decay time of glasses was in the millisecond order. There was thermal quenching observed in temperature-dependent luminescence (TDL). The radioluminescence (RL) and protonluminescence (PrL) represented the emission pattern of Dy3+ similarly to PL spectra. The concentration quenching caused 0.50Dy:NAGP glass with the highest PL and RL emission intensity. The X-ray imaging of developed glass using a synchrotron light source was successfully imaged for the first time.
Keywords: dysprosium; energy transfer; glass scintillator; X-ray imaging